Measurement and correlation of 4, 4′-dihydroxydiphenylsulfone solubility in ten neat organic solvents at temperatures from 278.15 to 313.15 K. (November 2022) - Mao, Haifang; Song, Liqin; Wang, Chaoyang; Zhang, Pingyi; Liu, Kejia; Tang, Ting; Jin, Miaomiao
Highlights: An isothermal saturation method was used to measure the solubility of BPS. Three mathematical models were used to correlate the experimental solubility data. The thermodynamic properties were calculated. Abstract: The equilibrium solubility of 4, 4′-dihydroxydiphenylsulfone (BPS) in ten neat organic solvents, including methanol, 2-butanol, acetonitrile, 2-butanone, cyclohexanone, formamide, N, N -dimethylformamide, ethyl formate, isopropyl acetate, and dimethyl carbonate at temperatures from 278.15 to 313.15 K under atmospheric pressure ( 101.3 × 10 3 Pa ) was studied using an isothermal saturation method. In all studied solvents, the solubility of BPS increased with the increase in temperature. Three solubility fitting models, including the van't Hoff equation, modified Apelblat equation, and λh equation, were used to correlate the experimental solubility data. The maximum magnitudes of the relative average deviation ( RAD% ) and root mean square deviation ( RMSD ) were 5.27 % and 9.45 × 10 -3 . Generally, the magnitudes of the RAD% generated by the modified Apelblat equation were the smallest among the selected solubility fitting models. The thermodynamic properties of BPS, such as the apparent standard dissolution enthalpy ( Δ H sol o ), standard dissolution Gibbs energy ( Δ G sol o ), and standard dissolution entropy change ( Δ S sol o ), were calculated. The Δ H sol o is positive in all studied cases, indicating that the dissolution process of BPS is endothermic. The obtained solubility data and relevant thermodynamic studies have an important guiding significance for optimizing the crystallization and purification process of BPS.